2000
DOI: 10.1002/(sici)1097-0290(20000420)68:2<211::aid-bit10>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Directed evolution of a novelN-carbamylase/D-hydantoinase fusion enzyme for functional expression with enhanced stability

Abstract: Bifunctional enzymes find a wide application as a monitoring facility and a potential biocatalyst in molecular biology and biotechnology. Recombination of natural enzymes to a bifunctional fusion offers valuable tools, but the functional and structural instability of artificial fusion enzymes remains to be solved. Based on structural traits of microbial D-hydantoinase, we attempted to construct a bifunctional N-carbamylase/Dhydantoinase fusion enzyme that would be useful for the synthesis of nonnatural D-amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…However, the fusion enzyme was unstable as a result of extensive proteolysis, and DNA shuffling was used subsequently to enhance the stability of the fusion enzyme. An evolved enzyme was identified that was six times as active as the parent fusion enzyme in converting the hydantoin into the D ‐amino acid 41. A direct comparison of the performance of the evolved fusion enzyme with the best available co‐expression system has yet to be reported.…”
Section: Enzymes As Biocatalystsmentioning
confidence: 99%
“…However, the fusion enzyme was unstable as a result of extensive proteolysis, and DNA shuffling was used subsequently to enhance the stability of the fusion enzyme. An evolved enzyme was identified that was six times as active as the parent fusion enzyme in converting the hydantoin into the D ‐amino acid 41. A direct comparison of the performance of the evolved fusion enzyme with the best available co‐expression system has yet to be reported.…”
Section: Enzymes As Biocatalystsmentioning
confidence: 99%
“…Hydantoinase was also subjected to directed evolution for enhanced stereochemical specificity and thermostability ( , ). Because of the potential commercial value of the structure-based design of the novel properties of these enzymes, both the l - and d -enantiomer specific hydantoinases were subjected to structural studies.…”
mentioning
confidence: 99%
“…However, it exhibited structural instability resulting in extensive proteolysis in vivo probably due to the low stability of the N‐terminal fusion partner, N‐carbamoylase. This unfavorable property of a fusion enzyme was improved by using DNA shuffling 58. Through three rounds of directed evolution, an evolved fusion enzyme with nine amino acid substitutions was obtained.…”
Section: Protein Engineering Of Hydantoinase‐related Enzymesmentioning
confidence: 99%